Detection and management of milk allergy: Delphi consensus study. Issue 7 (10th June 2022) - Allen, Hilary I.; Pendower, Ursula; Santer, Miriam; Groetch, Marion; Cohen, Mitchell; Murch, Simon H.; Williams, Hywel C.; Munblit, Daniel; Katz, Yitzhak; Gupta, Neeraj; Adil, Sabeen; Baines, Justine; et al.
Abstract: Background: There is significant overdiagnosis of milk allergy in young children in some countries, leading to unnecessary use of specialized formula. This guidance, developed by experts without commercial ties to the formula industry, aims to reduce milk allergy overdiagnosis and support carers of children with suspected milk allergy. Methods: Delphi study involving two rounds of anonymous consensus building and an open meeting between January and July 2021. Seventeen experts in general practice, nutrition, midwifery, health visiting, lactation support and relevant areas of paediatrics participated, located in Europe, North America, Middle East, Africa, Australia and Asia. Five authors of previous milk allergy guidelines and seven parents provided feedback. Findings: Participants agreed on 38 essential recommendations through consensus. Recommendations highlighted the importance of reproducibility and specificity for diagnosing milk allergy in children with acute or delayed symptoms temporally related to milk protein ingestion; and distinguished between children directly consuming milk protein and exclusively breastfed infants. Consensus was reached that maternal dietary restriction is not usually necessary to manage milk allergy, and that for exclusively breastfed infants with chronic symptoms, milk allergy diagnosis should only be considered in specific, rare circumstances. Consensus was reached that milk allergy diagnosis does not need to be considered for stool changes, aversive feeding or occasional spots of blood in stool, if there is no temporal relationship with milk protein ingestion. When compared with previous guidelines, these consensus recommendations resulted in more restrictive criteria for detecting milk allergy and a more limited role for maternal dietary exclusions and specialized formula. Interpretation: These new milk allergy recommendations from non‐conflicted, multidisciplinary experts advise narrower criteria, more prominent support for breastfeeding and less use of specialized formula, compared with current guidelines. Abstract : Milk allergy overdiagnosis is common in some regions and can potentially harm mothers and infants. We developed consensus recommendations for safe detection and management of milk allergy in young children. Recommendations aim to safely reduce overdiagnosis and better support breastfeeding women with suspected milk‐allergic infants (graphic created with BioRender.com).